Genome-wide expression analysis of novel heat-responsive microRNAs and their targets in contrasting wheat genotypes at reproductive stage under terminal heat stress - Saroha, Monika; Arya, Aditi; Singh, Gyanendra; Sharma, Pradeep (Frontiers in Plant Science, 2024)
Introduction Heat stress at terminal stage of wheat is critical and leads to huge yield losses worldwide. microRNAs (miRNAs) play significant regulatory roles in gene expression associated with abiotic and biotic stress at the post-transcriptional level. Methods In the present study, we carried out a comparative analysis of miRNAs and their targets in flag leaves as well as developing seeds of heat tolerant (RAJ3765) and heat susceptible (HUW510) wheat genotypes under heat stress and normal conditions using small RNA and degradome sequencing. Results and discussion A total of 84 conserved miRNAs belonging to 35 miRNA families and 93 novel miRNAs were identified in the 8 libraries. Tae-miR9672a-3p, tae-miR9774, tae-miR9669-5p, and tae-miR5048-5p showed the highest expression under heat stress. Tae-miR9775, tae-miR9662b-3p, tae-miR1120a, tae-miR5084, tae-miR1122a, tae-miR5085, tae-miR1118, tae-miR1130a, tae-miR9678-3p, tae-miR7757-5p, tae-miR9668-5p, tae-miR5050, tae-miR9652-5p, and tae-miR9679-5p were expressed only in the tolerant genotype, indicating their role in heat tolerance. Comparison between heat-treated and control groups revealed that 146 known and 57 novel miRNAs were differentially expressed in the various tissues. Eight degradome libraries sequence identified 457 targets of the differentially expressed miRNAs. Functional analysis of the targets indicated their involvement in photosynthesis, spliceosome, biosynthesis of nucleotide sugars and protein processing in the endoplasmic reticulum, arginine and proline metabolism and endocytosis. Conclusion This study increases the number of identified and novel miRNAs along with their roles involved in heat stress response in contrasting genotypes at two developing stages of wheat.